On exact special solutions for the stochastic regularized long wave-Burgers equation - Korpinar, Zeliha; İnç, Mustafa; Alshomrani, Ali S.; Baleanu, Dumitru (Springer, 2020)
In this paper, we will analyze the Regularized Long Wave-Burgers equation with conformable derivative (cd). Some white noise functional solutions for this equation are obtained by using white noise analysis, Hermite transforms, and the modified sub-equation method. These solutions include exact stochastic trigonometric functions, hyperbolic functions solutions and wave solutions. This study emphasizes that the modified fractional sub-equation method is sufficient to solve the stochastic nonlinear equations in mathematical physics.
Keywords: The stochastic RLWBE; White noise analysis; Hermite transforms; The modified sub-equation method